Misunderstanding of Council Action on Proposed City-County Airport Agreement - Paul E. Wolven:::::: (1971)
A memorandum informing Oxnard City Council of a misunderstanding made by the press in regards to a vote moved to temporarily leave Oxnard Air Base as it is and not participate in any more agreements with Ventura County.